Catalyst for syngas production and a method using the same - Yap, Taufiq Yun Hin; Sudarno, (2012)
A catalyst of producing syngas by dry reforming of methane and carbon dioxide comprises a support prepared from CeO2-SiO2; and nickel nano-particles dispersed onto the surface of the support.